COVID-19 and the impact of physical activity on persistent symptoms - Lauren E. Opielinski; Toni D. Uhrich; Toni D. Uhrich; Toni D. Uhrich; Michael H. Haischer; Michael H. Haischer; Rachel N. Beilfuss; Lindsey M. Mirkes Clark; Lindsey M. Mirkes Clark; Kamryn M. Kroner; Rachel E. Bollaert; Michael J. Danduran; et al. (Frontiers in Sports and Active Living)
IntroductionPhysical activity is protective against chronic disease but whether activity is associated with persistent symptoms in non-hospitalized coronavirus disease 2019 (COVID-19) survivors is unknown. The purpose of the study was to determine the impact of the COVID-19 pandemic on physical activity levels and the influence of physical activity on acute COVID-19 and long COVID symptoms in non-hospitalized COVID-19 survivors.MethodsIn total, 64 non-hospitalized COVID-19 survivors (45 female participants, 40 ± 18 years) were assessed for activity levels, body composition, and symptoms of COVID-19 8.5 ± 4.7 months post-infection and categorized into two groups: (1) persistent symptoms and (2) no symptoms at the time of testing. Furthermore, 43 of the 64 participants (28 female participants, 46 ± 18 years) completed a follow-up questionnaire online 51.0 ± 39.7 months (4.25 years) post-infection. A subset of 22 COVID-19 survivors (16 female participants, 35 ± 16 years) were matched for age, sex, and body mass index with healthy controls. Physical activity was quantified using (1) self-reported questionnaire (International Physical Activity Questionnaire; IPAQ-SF) at three time periods; prior to COVID-19 infection, at the time of laboratory testing (8.5 ± 4.7 months after infection), and during an online follow-up (51.0 ± 39.7 months, i.e., 4.25 years after infection); and (2) 7 days of wearing an ActiGraph accelerometer following laboratory testing.ResultsPhysical activity (IPAQ-SF) declined in COVID-19 survivors from pre-COVID-19 infection to 8.5 ± 4.7 months after infection [3,656 vs. 2,656 metabolic equivalent of task (MET) min/week, 27% decrease, p < 0.001, n = 64] and rebounded to levels similar to pre-COVID-19 infection at 4.25 years after infection (p = 0.068, n = 43). Activity levels quantified with accelerometry did not differ between COVID-19 survivors and controls. However, COVID-19 survivors who reported persistent symptoms 8.5 months after infection (n = 29) engaged in less moderate-vigorous physical activity and steps/day than those without persistent symptoms (n = 27) (37 vs. 49 MET min/day, p = 0.014 and 7,915 vs. 9,540 steps/day, p = 0.014).DiscussionBoth COVID-19 survivors and matched controls reported reductions in physical activity indicating that lower levels of activity were likely due to the pandemic rather than COVID-19 infection alone. However, those who were most affected by COVID-19 infection with persistent symptoms had the greatest reductions in physical activity, even at ∼8 months and ∼4 years post-infection.